Yiqi Huoxue Recipe Improves Heart Function through Inhibiting Apoptosis Related to Endoplasmic Reticulum Stress in Myocardial Infarction Model of Rats. (17th April 2014) - Lou, Li-Xia; Wu, Ai-Ming; Zhang, Dong-Mei; Wu, Sheng-Xian; Gao, Yong-Hong; Nie, Bo; Zhao, Ming-Jing; Lv, Xi-Ying; Jin, Qiu-Shuo; Zhao, Yi-Zhou; Wang, Shuo-Ren; Chai, Li-Min
Abstract : Objective . To explore the mechanism of cardioprotective effects of Chinese medicine, Yiqi Huoxue recipe, in rats with myocardial infarction- (MI-) induced heart failure. Methods . Male Sprague-Dawley rats underwent left anterior descending artery (LAD) ligation or sham operation. The surviving MI rats were divided randomly into three groups: MI (5 mL/kg/d NS by gavage), MI + Metoprolol Tartrate (MT) (12 mg/kg/d MT by gavage), and MI + Yiqi Huoxue (5 mL/kg recipe by gavage). And the sham operation rats were given 5 mL/kg/d normal saline. Treatments were given on the day following surgery for 4 weeks. Then rats were detected for heart structure and function by transthoracic echocardiography. Apoptosis in heart tissues was detected by TUNEL staining. To determine whether the endoplasmic reticulum (ER) stress response pathway is included in the cardioprotective function of the recipe, ER stress related proteins such as GRP78 and caspase-12 were examined. Results . Yiqi Huoxue recipe attenuated heart function injury, reversed histopathological damage, alleviated myocardial apoptosis and inhibited ER stress in MI rats. Conclusion . All the results suggest that Yiqi Huoxue recipe improves the injured heart function maybe through inhibition of ER stress response pathway, which is a promising target in therapy for heart failure.